2020
DOI: 10.1016/j.cedpsych.2020.101901
|View full text |Cite
|
Sign up to set email alerts
|

Same mindset, different goals and motivational frameworks: Profiles of mindset-based meaning systems

Abstract: Profile analyses of mindset-related constructs yielded a four-profile solution. Growth mindset was accompanied by either high mastery goals or high multiple goals. Fixed mindset was accompanied by either high performance goals or low all goals. Profiles with a growth mindset performed better on high-stakes exams. Boys were more commonly found in profiles underpinned by a fixed mindset.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 79 publications
4
17
0
Order By: Relevance
“…Future neuroscience studies can contribute to refining theoretical models of mindset by exploring potential contextual influences and individual variation. This fits in recent attempts by other researchers to investigate more nuanced relationships between mindset and associated constructs, such as achievement goals, using latent profile analysis [45]. It would be particularly interesting to associate different mindset profiles to neurocognitive processes, such as error-monitoring.…”
Section: Discussionsupporting
confidence: 66%
“…Future neuroscience studies can contribute to refining theoretical models of mindset by exploring potential contextual influences and individual variation. This fits in recent attempts by other researchers to investigate more nuanced relationships between mindset and associated constructs, such as achievement goals, using latent profile analysis [45]. It would be particularly interesting to associate different mindset profiles to neurocognitive processes, such as error-monitoring.…”
Section: Discussionsupporting
confidence: 66%
“…Based on previous research and theoretical discussion regarding mindset systems (Dweck & Molden, 2013;Yu & McLellan, 2020), we expect to identify at least three profiles, representing two extreme ends of the fixed versus growth systems, and at least one profile that is qualitatively different from fixed and growth systems (e.g., Chen & Tutwiler, 2017;Yu & McLellan, 2020). According to research showing that mindsets indirectly predict engagement and achievement through associated constructs such as goals and persistence (e.g., Blackwell et al, 2007;Lee & Seo, 2019), we hypothesize that profiles with a growth mindset (accompanied with mastery goals, persistence, and positive reappraisal in challenges) will be associated with the highest engagement and achievement.…”
Section: Research Questionsmentioning
confidence: 99%
“…So far, no studies have examined mindset profiles within the domain of L2, but we identified three published studies using a person-centered approach with mindsets in the domains of science (Chen, 2012; Chen & Tutwiler, 2017), math (Yu & McLellan, 2020), and language arts/first language literacy (Yu & McLellan, 2020). First, Chen (2012) identified four profiles based on high school students’ science mindsets and epistemic beliefs about the nature of science.…”
Section: A Person-centered Approach To the Mindset Systemmentioning
confidence: 99%
“…45 For example, a growth mindset helps people stay focused on their goals, 46 and influences individuals' strategies which they have used to cope with the barriers encountered in implementing their goals and the ways in which they seek and do their jobs. 47 Growth mindset about work can be conceived of as a psychological strength that manifests as personal agency in career development. It plays a critical role in energizing the problem-solving process and continued goal pursuit when faced with challenges.…”
Section: Growth Mindset About Work and Living A Callingmentioning
confidence: 99%